PERBANDINGAN KEBERFUNGSIAN DISTRAKTOR DALAM TES: PENDEKATAN TEORI TES KLASIK DAN MODERN DALAM KONTEKS PENDIDIKAN SEKOLAH DASAR - Syahrial Syahrial; Nurhudayah M; Suyit Ratno; Andri K Sitanggang (Universitas Negeri Medan, 2023)
This study aims to examine the characteristics of formative test items in elementary schools by comparing the functionality of distractors based on classical and modern test theories. This research is a quantitative descriptive study. The data collection technique used in this study was documentation. The results of the analysis indicate that out of 25 test items, 16% were easy, 72% were moderate, and 12% were difficult, with 3 items not fitting. The measurement results using modern test theory showed that 60% of the distractors were not functioning effectively, and 24% of the items needed to have their answer keys checked, while the measurement using classical test theory showed that 56% of the distractors were not functioning effectively, and 12% of the items needed to have their answer keys checked. Less effective distractors indicate that they are selected more frequently by high-ability groups than low-ability groups. In this context, compared to classical test theory, modern Rasch model is capable of providing more complex results and detecting a greater number of ineffectively functioning distractors. However, in its implementation, the modern Rasch model is more challenging than classical test theory.